A Diagnostic Analysis of Observational Sketching: Examples from the University of Latvia - Urdziņa-Deruma, Māra; Celmiņa-Ķeirāne, Austra; Avotiņa, Austra; Karlsone, Inguna (Acta Paedagogica Vilnensia, 2023)
The importance of freehand sketching is being updated and revised at a time when sketching by hand is, in many cases, being replaced by sketching with digital technologies. In addition, in Latvia, since the reform of the general education curriculum, sketching has been included in the new primary education curriculum, which requires primary school teachers to have experience and understanding of sketching. Freehand sketching is also part of the curriculum for future designers’ education. Researchers at the University of Latvia developed a task, criteria, and a description of the assessment levels (rubric) for sketching from an image to assess the initial preparedness and observational sketching skills of students on design and primary school education teachers’ programmes. The conclusion was that students’ sketching skills could be developed and extended by encouraging the use of different technical approaches and means of expression, as well as by practising the accuracy of observation.